Lithium-ion batteries and electronic devices
By controlling the hydrogen content in silicon carbon materials and depositing nanosilicon on the porous carbon framework, the problem of volume expansion of silicon negative electrode materials and side reactions of hydrogen elements in lithium-ion batteries is solved, and the long-term cycle stability and performance improvement of the battery is achieved.
Patent Information
- Application Number
- CN202211233092.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-10
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-10-10
AI Technical Summary
The volume expansion of the silicon negative electrode material in lithium-ion batteries during charging and discharging leads to the pulverization of the electrode sheet and the SEI film instability, which in turn causes capacity attenuation. At the same time, the hydrogen element introduced during nanosilicon deposition leads to side reactions with the electrolyte, which consumes lithium hexafluorophosphate and active silicon.
By controlling the hydrogen content in silicon carbon materials within the range of 0.1≤a≤5%, the side reaction between the surface of silicon carbon materials and the electrolyte is reduced. Porous carbon is used as the framework to deposit nanosilicon in its pores, and the pore size distribution and nanosilicon size are regulated to buffer volume expansion.
It improves the long-term cycle stability of lithium-ion batteries, extends the cycle life of the battery, reduces capacity attenuation, and improves rate performance and first-term effect.
Smart Images

Figure QLYQS_1 
Figure GDA0004980762500000081 
Figure GDA0004980762500000191
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a lithium-ion battery and an electronic device. Background Art
[0002] Silicon, as the negative electrode material of lithium-ion batteries, has a theoretical capacity of up to 4200mAh / g. It is considered to be the next generation of lithium-ion negative electrode materials that is most likely to replace traditional graphite negative electrode materials and thus improve the energy density of lithium-ion batteries. However, during the charge and discharge process, as lithium ions are embedded in the silicon lattice, silicon-silicon bonds break, and lithium-silicon bonds are gradually generated. Silicon particles will undergo a huge volume expansion (300-400%) during the lithium embedding process. This huge volume expansion is inevitable during the lithium embedding process of silicon particles. The change in volume during the cycle will cause the silicon particles to break, which in turn causes the pole piece to pulverize and form an unstable SEI film, resulting in rapid capacity decay.
[0003] In addition, the preparation process of silicon materials, such as the deposition process of nano-silicon, is actually the process of dehydrogenation of silane, which will introduce hydrogen elements and easily form -OH endings. The -OH functional group can easily react with free H in the electrolyte to generate water, which then reacts with lithium hexafluorophosphate in the electrolyte additive to consume lithium hexafluorophosphate. At the same time, the generated hydrofluoric acid will react with active silicon, causing irreversible consumption of silicon and deteriorating cycle performance. Therefore, in addition to precise structural design and reserved expansion space for silicon, solving the interface problem between it and the electrolyte is also the key to obtaining long-term cycle stability. Summary of the invention
[0004] The present application provides a lithium-ion battery and an electronic device, which controls the hydrogen content in the silicon-carbon material within a certain range, reduces the side reaction between the surface of the silicon-carbon material and the electrolyte, and helps to improve the long-term cycle stability of the lithium-ion battery.
[0005] In a first aspect, the present application provides a lithium-ion battery, the lithium-ion battery comprising a negative electrode plate, the negative electrode plate comprising a silicon-carbon material, the silicon-carbon material containing hydrogen, based on the mass of the silicon-carbon material, the mass percentage of the hydrogen is a%, and 0.1≤a≤5. When the total H element content in the silicon-carbon material is too large, the surface of the silicon-carbon material has a large amount of free -OH, which is not conducive to improving the cycle performance of the lithium-ion battery. Therefore, it is necessary to control the H element content inside the silicon-carbon material within an appropriate range.
[0006] In some embodiments, the mass percentage of the hydrogen element is a%, and 0.5≤a≤3. In this case, the cycle performance of the lithium-ion battery is improved.
[0007] In some embodiments, the hydrogen element in the silicon-carbon material includes active hydrogen and inactive hydrogen; 0.5 g of the silicon-carbon material is placed in a 36 ml reaction bottle, and reacted at 70° C. for 48 hours to dissociate the active hydrogen in the Si-H bond into hydrogen, and then the mixed gas in the reaction bottle is obtained, and the volume percentage of hydrogen in the mixed gas is x, and the mass of active hydrogen in 0.5 g of the silicon-carbon material is y; satisfying:
[0008] (1) 1% ≤ x ≤ 40%;
[0009] (2)
[0010] The silicon-carbon material is obtained by depositing nano-silicon in the pores of porous carbon. By adjusting the relationship between the pore size distribution, pore volume, and nano-silicon size and content, the energy density of silicon can be increased while ensuring sufficient volume expansion buffer space. However, the deposition process of nano-silicon is actually a dehydrogenation process of silane. After the silane dissociates, Si and H are generated. 2 , and the vacant bonds on the Si atoms and the free H in the deposition process will form new Si-H bonds. The active hydrogen refers to the hydrogen that can be dissociated from the Si-H bond, and the inactive hydrogen refers to the hydrogen that cannot be dissociated from the Si-H bond. Since the Si-H bond easily forms an -OH ending, the -OH functional group in the electrolyte can easily react with the free H in the electrolyte to generate water, and then the water reacts with the lithium hexafluorophosphate in the electrolyte additive to consume the lithium hexafluorophosphate. At the same time, the generated hydrofluoric acid will react with the active silicon, causing irreversible consumption of silicon. The present application can reduce the side reaction of the -OH functional group on the silicon surface with the electrolyte and improve the long-term cycle stability of lithium-ion batteries by controlling the content of active hydrogen in the silicon-carbon material within a suitable range.
[0011] The volume percentage x of hydrogen in the mixed gas is related to the test method, and the x value in this application needs to be obtained under a specific test method: use a 2.5mL gas injection needle to extract 1mL of the mixed gas from the reaction bottle for GC-TCD testing, the testing equipment is Aglient 7890A, the injection port temperature is 150°C, the constant flow mode is used for splitting, the carrier gas is helium, the chromatographic column flow rate is 8ml / min, the split ratio is 2:1, the detector temperature is 200°C, the reference flow rate is 30mL / min, and the tail gas flow is 4mL / min; the test principle is to use gas chromatography, when the sample enters the chromatographic column and runs, the components are repeatedly distributed between the two phases, due to the different adsorption capacities of the fixed phase to each component, after a certain column length, the components are separated from each other, leave the chromatographic column in the order of elution and enter the detector for detection, and the chromatographic peak elution curve of each component is drawn on the recorder. By testing the peak area and using the external standard method for quantification, the volume fraction of each component can be determined, and then the volume percentage x of hydrogen in the mixed gas can be obtained.
[0012] In some embodiments, the lithium ion battery satisfies: 2%≤x≤15%. In this case, the battery has good cycle performance.
[0013] In some embodiments, in the silicon-carbon material, the ratio of the mass of the active hydrogen yμg to the mass percentage of the hydrogen element a% is z, z=y / a, and satisfies: 2%≤z≤30%. If the ratio of the mass of the active hydrogen to the mass of the hydrogen element is too large, it means that there are more -OH groups on the surface of the silicon particles, and the -OH groups will react with the free H in the electrolyte to generate water, which will then react with the lithium salt additive in the electrolyte to generate hydrofluoric acid, which will further react with silicon, resulting in the loss of active silicon and deterioration of electrical properties.
[0014] In some embodiments, the lithium-ion battery satisfies: 3%≤z≤22%. At this time, the ratio of the mass of active hydrogen in the silicon-carbon material to the mass of hydrogen element is further controlled within a suitable range, which is conducive to improving the cycle performance of the lithium-ion battery.
[0015] In some of the embodiments, based on the mass of the silicon-carbon material, the mass percentage of the hydrogen element is a%, and 0.5≤a≤3.
[0016] In some embodiments, in the silicon-carbon material, the mass percentage of silicon is b%, and the value range of b satisfies: 10≤b≤90; in the silicon-carbon material, the ratio of the mass percentage of hydrogen a% to the mass percentage of silicon b% is a / b, which satisfies: 0.001≤a / b≤0.5. Although the effect of increasing the content of silicon on gas production is not very large, the amount of gas production is the amount of 0.5g of the silicon-carbon material placed in a 36ml reaction bottle and reacted at 70°C for 48h to dissociate the active hydrogen in the Si-H bond into hydrogen, but too much silicon content will lead to increased volume expansion, which is not conducive to improving cycle performance.
[0017] In some embodiments, the lithium-ion battery satisfies at least one of the following conditions: (1) 45≤b≤52; (2) 0.01≤a / b≤0.05. In this case, the silicon content ratio is appropriate, and the mass ratio of the hydrogen element to the silicon element is also within an appropriate range, which is conducive to further improving the cycle performance of the lithium-ion battery.
[0018] In some embodiments, in the silicon-carbon material, the mass percentage of carbon is c%, and satisfies: 10≤c≤80; in the silicon-carbon material, the ratio of the mass percentage of carbon c% to the mass percentage of silicon b% is c / b, and satisfies: 0.1≤c / b≤8. When the content of carbon is low, it is not conducive to providing sufficient buffer space for the expansion of silicon particles, thereby causing deterioration of the cycle performance; a suitable carbon-silicon ratio is conducive to improving the cycle performance and expansion performance of lithium-ion batteries.
[0019] In some embodiments, the following conditions are satisfied: 40≤c≤55; and 0.8≤c / b≤1.2. In this case, the cycle performance of the lithium-ion battery can be further improved and the expansion can be suppressed.
[0020] In some embodiments, the mass percentage of oxygen in the silicon-carbon material is e%, satisfying: 0.1≤e≤10. A suitable content of oxygen is beneficial to improving the first cycle coulomb efficiency (first efficiency) of the lithium-ion battery. Excessive oxygen content will consume active lithium and form an inert phase, which will deteriorate the first efficiency.
[0021] In some embodiments, the lithium ion battery satisfies: 0.2≤e≤6. In this case, the lithium ion battery has a higher first efficiency.
[0022] In some embodiments, in the silicon-carbon material, the ratio of the mass yμg of the active hydrogen to the mass percentage d% of lithium hexafluorophosphate in the lithium ion battery is y / (d%), which satisfies: 0.075≤y / (d%)≤55. Lithium hexafluorophosphate serves as a bridge between positive and negative lithium ions. An appropriate content of lithium hexafluorophosphate is beneficial to improving lithium ion transfer kinetics and rate performance. At the same time, abundant lithium salts can ensure the bridge effect and maintain cycle performance.
[0023] In some embodiments, the lithium ion battery satisfies at least one of the following conditions: (1) 5≤d≤40; (2) 0.5≤y / (d%)≤8. In this case, better cycle performance and rate performance can be obtained.
[0024] In a second aspect, the present application provides a method for preparing the above-mentioned lithium-ion battery, in particular a method for preparing the silicon-carbon material in the lithium-ion battery, comprising at least the following steps:
[0025] (1) obtaining a porous carbon skeleton: the pore volume is 0.5 to 1 g / cc, wherein the pore volume of micropores and mesopores is 75 to 90%;
[0026] (2) subjecting the porous carbon skeleton to a silane deposition reaction to obtain an intermediate product;
[0027] (3) The intermediate product is subjected to a passivation reaction to obtain the silicon-carbon material.
[0028] In some of the embodiments, in step (2), the conditions of the silane deposition reaction include: introducing silane gas with a volume content of 10 to 35% at 400 to 1000° C., with other gas components being inert gases, and the reaction time being 5 to 15 hours.
[0029] In some embodiments, in step (3), the conditions of the passivation reaction include: introducing 5-30% oxygen by volume at 45-205° C., the other gas components are inert gases, and the reaction time is 5-15 hours. The inert gas in steps (2) and (3) can be one of nitrogen, argon, helium, or a combination thereof.
[0030] The present application obtains a porous silicon-carbon composite (i.e., silicon-carbon material) by depositing silane in porous carbon with a special pore structure. In particular, by controlling the process conditions of the silane deposition reaction and the passivation process after deposition, the hydrogen content of the porous silicon-carbon composite is controlled within a certain range, and the Si-H bond easily forms an -OH ending, thereby reducing the side reaction between the -OH functional group on the silicon surface and the electrolyte, thereby improving the long-term cycle stability of the lithium-ion battery.
[0031] In a third aspect, the present application provides an electronic device, wherein the electronic device comprises any one of the above-mentioned lithium-ion batteries or a lithium-ion battery prepared by any one of the above-mentioned preparation methods.
[0032] The beneficial effects brought about by the technical solutions provided in some embodiments of the present application include at least: by controlling the content of active hydrogen in the silicon-carbon material within a suitable range, the side reaction between the -OH functional group on the surface of the silicon-carbon material and the electrolyte can be reduced, thereby improving the long-term cycle stability of the lithium-ion battery; at the same time, controlling the content of silicon, carbon and oxygen in the silicon-carbon material within a suitable range is beneficial to improving the cycle performance, reducing expansion, improving the rate performance and improving the first efficiency. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.
[0034] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0035] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C.
[0036] In the initial industrialization, nano-silicon was evenly dispersed in graphite or other carbon phases in the hope that graphite and carbon could buffer the volume expansion of silicon. However, the elasticity of graphite and carbon is limited and cannot effectively buffer the expansion stress of silicon. Although it has been applied in hard-shell cylindrical batteries, it cannot be applied in soft-pack batteries. At the same time, the amount of silicon added is limited, and the advantage of silicon's high energy density cannot be effectively utilized. To this end, in recent years, researchers have designed more sophisticated structures by introducing porous carbon and depositing nanosilicon in the pores of porous carbon. By regulating the relationship between pore size distribution, pore volume and nanosilicon size and content, the energy density of silicon can be improved while ensuring sufficient buffer space for volume expansion, thereby obtaining better cycle performance than traditional encapsulation structures. However, in the silane deposition process, which is actually a dehydrogenation process of silane, Si-H bonds will be formed, that is, hydrogen elements will be introduced. When it comes into contact with water in the air or water in an aqueous formula, it is easy to form an -OH ending. The -OH functional group can easily react with free H in the electrolyte to generate water, and then the water reacts with lithium hexafluorophosphate in the electrolyte additive to consume lithium hexafluorophosphate. At the same time, the generated hydrofluoric acid will react with active silicon, causing irreversible consumption of silicon and deteriorating the cycle performance.
[0037] Lithium-ion battery
[0038] In order to solve the above technical problems, the present application proposes a lithium-ion battery, including a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte.
[0039] Negative electrode
[0040] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material in the negative electrode active material layer includes a silicon-carbon material, wherein the silicon-carbon material contains hydrogen, and based on the mass of the silicon-carbon material, the mass percentage of the hydrogen is a%, and 0.1≤a≤5. When the total H element content in the silicon-carbon material is too large, the surface of the silicon-carbon material has a large amount of free -OH, which is not conducive to improving the cycle performance of the lithium-ion battery. Therefore, the H element content inside the silicon-carbon material needs to be controlled within an appropriate range.
[0041] In some embodiments, the mass percentage of the hydrogen element in the silicon-carbon material is a%, and the value range of a satisfies: 0.1≤a≤5.
[0042] Exemplarily, the mass percentage a% of the hydrogen element is 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range consisting of any two of the above values.
[0043] In some embodiments, the mass percentage of the hydrogen element in the silicon-carbon material is a%, satisfying: 0.5≤a≤3.
[0044] Exemplarily, the mass percentage a% of the hydrogen element is 0.5%, 0.6%, 0.7%, 0.9%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3% or a range consisting of any two of the above values.
[0045] The hydrogen element includes active hydrogen and inactive hydrogen; 0.5 g of the silicon-carbon material is placed in a 36 ml reaction bottle, and reacted at 70° C. for 48 h to dissociate the active hydrogen in the Si-H bond into hydrogen gas, and then the mixed gas in the reaction bottle is obtained, and the volume percentage of hydrogen gas in the mixed gas is x, and the mass of active hydrogen in the silicon-carbon material is y μg; satisfying: (1) 1% ≤ x ≤ 40%; (2)
[0046]
[0047] Exemplarily, the volume percentage x of hydrogen in the mixed gas is 1%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or a range consisting of any two of the above values.
[0048] In some embodiments, the test method includes: using a 2.5mL gas injection needle to extract 1mL of mixed gas from the reaction bottle for GC-TCD testing, the test equipment is Aglient 7890A, the injection port temperature is 150°C, the constant flow mode is used for splitting, the carrier gas is helium, the chromatographic column flow rate is 8ml / min, the split ratio is 2:1, the detector temperature is 200°C, the reference flow is 30mL / min, and the tail gas flow is 4mL / min.
[0049] In some embodiments, the volume percentage x of hydrogen in the mixed gas satisfies: 2%≤x≤15%.
[0050] Exemplarily, the volume percentage x of hydrogen in the mixed gas is 2%, 4%, 6%, 8%, 10%, 12%, 13%, 15% or a range consisting of any two of the above values.
[0051] In some embodiments, the ratio of the mass yμg of the active hydrogen in the silicon-carbon material to the mass percentage content a% of the hydrogen element is z, z=y / a, satisfying: 2%≤z≤30%.
[0052] Exemplarily, the ratio z of the mass yμg of the active hydrogen to the mass percentage content a% of the hydrogen element is 2%, 4%, 6%, 8%, 10%, 15%, 20%, 25%, 30% or a range consisting of any two of the above values.
[0053] In some embodiments, the ratio of the mass yμg of the active hydrogen in the silicon-carbon material to the mass percentage content a% of the hydrogen element is z, z=y / a, satisfying: 3%≤z≤22%.
[0054] Exemplarily, the ratio z of the mass of the active hydrogen to the mass of the hydrogen element is 3%, 5%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22% or a range consisting of any two of the above values.
[0055] In some embodiments, the mass percentage of silicon in the silicon-carbon material is b%, and the value range of b satisfies: 10≤b≤90;
[0056] The ratio of the mass percentage content a% of the hydrogen element in the silicon-carbon material to the mass percentage content b% of the silicon element is a / b, which satisfies: 0.001≤a / b≤0.5.
[0057] Exemplarily, the mass percentage b% of the silicon element is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or a range consisting of any two of the above values.
[0058] Illustratively, the ratio a / b of the mass percentage a% of the hydrogen element to the mass percentage b% of the silicon element is 0.001, 0.01, 0.1, 0.2, 0.3, 0.4, 0.5 or a range consisting of any two of the above values.
[0059] In some embodiments, the mass percentage b of the silicon element in the silicon-carbon material and the ratio a / b of the mass percentage a% of the hydrogen element to the mass percentage b% of the silicon element satisfy at least one of the following conditions:
[0060] (1)45≤b≤52;
[0061] (2)0.01≤a / b≤0.05.
[0062] Exemplarily, the mass percentage b% of the silicon element is 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52% or a range consisting of any two of the above values.
[0063] Illustratively, the ratio a / b of the mass percentage content a% of the hydrogen element to the mass percentage content b% of the silicon element is 0.01, 0.02, 0.03, 0.04, 0.05 or a range consisting of any two of the above values.
[0064] In some embodiments, the mass percentage of carbon element in the silicon-carbon material is c%, and the value range of c satisfies: 10≤c≤80; the ratio of the mass percentage of carbon element c% to the mass percentage of silicon element b% in the silicon-carbon material is c / b, which satisfies: 0.1≤c / b≤8.
[0065] Exemplarily, the mass percentage c% of the carbon element is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or a range consisting of any two of the above values.
[0066] Illustratively, the ratio c / b of the mass percentage content c% of the carbon element to the mass percentage content b% of the silicon element is 0.1, 0.5, 1, 3, 5, 8 or a range consisting of any two of the above values.
[0067] In some embodiments, 40≤c≤55 is satisfied; and 0.8≤c / b≤1.2 is satisfied.
[0068] Exemplarily, the mass percentage c% of the carbon element is 40%, 45%, 50%, 55% or a range consisting of any two of the above values.
[0069] Illustratively, the ratio c / b of the mass percentage content c% of the carbon element to the mass percentage content b% of the silicon element is 0.8, 0.9, 1, 1.1, 1.2 or a range consisting of any two of the above values.
[0070] In some embodiments, the mass percentage of oxygen in the silicon-carbon material is e%, satisfying: 0.1≤e≤10.
[0071] Exemplarily, the mass percentage e% of the oxygen element is 0.1%, 1%, 2%, 4%, 6%, 8%, 10% or a range consisting of any two of the above values.
[0072] In some embodiments, the mass percentage of oxygen in the silicon-carbon material is e%, satisfying: 0.2≤e≤6.
[0073] Exemplarily, the mass percentage e% of the oxygen element is 0.2%, 0.4%, 0.6%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6% or a range consisting of any two of the above values.
[0074] In some embodiments, the ratio of the mass y of the active hydrogen in the silicon-carbon material to the mass percentage d% of lithium hexafluorophosphate in the lithium-ion battery is y / (d%), satisfying: 0.075≤y / (d%)≤55.
[0075] Exemplarily, the ratio y / (d%) of the mass y of the active hydrogen to the mass percentage d% of lithium hexafluorophosphate in the lithium ion battery is 0.075, 0.1, 1, 5, 10, 20, 30, 40, 50, 55 or a range consisting of any two of the above values.
[0076] In some embodiments, the mass y of the active hydrogen in the silicon-carbon material and the mass percentage d% of lithium hexafluorophosphate in the lithium-ion battery satisfy at least one of the following conditions:
[0077] (1)5≤d≤40; (2)0.5≤y / (d%)≤8.
[0078] Exemplarily, the mass percentage d% of the lithium hexafluorophosphate is 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or a range consisting of any two of the above values.
[0079] Illustratively, the ratio y / (d%) of the mass y of the active hydrogen to the mass percentage d% of the lithium hexafluorophosphate is 0.5, 0.8, 1, 3, 5, 7, 8 or a range consisting of any two of the above values.
[0080] The preparation method of the silicon-carbon material:
[0081] (1) obtaining a porous carbon skeleton: the pore volume is 0.5 to 1 g / cc, wherein the pore volume of micropores and mesopores is 75 to 90%;
[0082] (2) subjecting the porous carbon skeleton to a silane deposition reaction to obtain an intermediate product;
[0083] The conditions of the silane deposition reaction include: introducing silane gas with a volume content of 10 to 35% at 400 to 1000° C., other gas components being inert gas, and a reaction time of 5 to 15 hours.
[0084] (3) The intermediate product is subjected to a passivation reaction to obtain the silicon-carbon material.
[0085] The conditions of the passivation reaction include: introducing oxygen with a volume content of 5 to 30% at 45 to 205° C., with other gas components being inert gas, and reacting for 5 to 15 hours to obtain the product.
[0086] The negative electrode current collector may be made of metal foil or porous metal plate, for example, foil or porous plate made of metal such as copper, nickel, titanium or iron or alloys thereof, such as copper foil.
[0087] The negative electrode sheet can be prepared according to conventional methods in the art.
[0088] Exemplarily, graphite, the prepared silicon-carbon material, and a conductive agent (conductive carbon black, ) and binder PAA are mixed in a weight ratio of about 70%:15%:5%:10%, an appropriate amount of water is added, and the mixture is kneaded at a solid content of about 55wt% to 70wt%, and an appropriate amount of water is added to adjust the viscosity of the slurry to about 4000 to 6000Pa·s to prepare a negative electrode slurry. The prepared negative electrode slurry is coated on a negative electrode current collector copper foil, dried, and cold pressed to obtain a negative electrode sheet.
[0089] Positive electrode
[0090] The positive electrode plate includes a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector. The positive electrode active material in the positive electrode active material layer can be selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate and compounds obtained by adding other transition metals or non-transition metals to the above compounds.
[0091] For example, the positive electrode current collector may be made of a metal foil or a porous metal plate, for example, a foil or a porous plate made of a metal such as aluminum, copper, nickel, titanium or iron, or an alloy thereof, such as Al (aluminum) foil.
[0092] The positive electrode sheet can be prepared according to conventional methods in the art.
[0093] For example, LiCoO 2 , conductive carbon black and polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system in a weight ratio of about 95%:2.5%:2.5% to obtain a positive electrode slurry, and the prepared positive electrode slurry is coated on a positive electrode current collector aluminum foil, dried, and cold pressed to obtain a positive electrode sheet.
[0094] Isolation film
[0095] There is no specific limitation on the type of the isolation film, which can be selected according to actual needs. For example, the isolation film can be a polyethylene film, a polypropylene film, a polyvinylidene fluoride film, and a multilayer composite film thereof, but is not limited to these materials.
[0096] The isolation membrane can be prepared according to conventional methods in the art.
[0097] Exemplarily, the isolation membrane substrate is 8 μm thick polyethylene (PE), and a 2 μm alumina ceramic layer is coated on both sides of the isolation membrane substrate. Finally, 2.5 mg of binder polyvinylidene fluoride (PVDF) is coated on both sides of the ceramic layer and dried.
[0098] Electrolyte
[0099] The electrolyte includes an organic solvent, an electrolyte lithium salt (lithium hexafluorophosphate) and an additive. The present invention does not impose any specific restrictions on the type of the electrolyte, and the electrolyte can be selected according to actual needs.
[0100] Exemplarily, the organic solvent includes one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) or diethyl sulfone (ESE), preferably two or more.
[0101] The electrolyte may also optionally include other additives, which may be any additive that can be used as a lithium ion secondary battery. The present invention is not specifically limited and may be selected according to actual needs. As an example, the additive may be one or more of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), succinonitrile (SN), adiponitrile (AND), 1,3-propylene sultone (PST), sulfonate cyclic quaternary ammonium salt, tris(trimethylsilyl) phosphate (TMSP) or tris(trimethylsilyl) borate (TMSB).
[0102] The above electrolyte can be prepared according to conventional methods in the art.
[0103] For example, in a dry argon environment, LiPF was added to a solvent of propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) (mass ratio 1:1:1). 6 Mix well to obtain an electrolyte solution, wherein LiPF 6 The mass percentage is 13%.
[0104] Preparation of lithium-ion batteries
[0105] The positive electrode sheet, isolation film and negative electrode sheet are stacked in order, so that the isolation film is placed between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the qualified bare battery cell is welded to the top cover through the pole ear, placed in the outer packaging shell, and injected with electrolyte after drying, and a lithium-ion battery is obtained through a process of formation, degassing, trimming and the like.
[0106] Electronic devices
[0107] The electronic equipment of the present application includes any one of the above-mentioned lithium-ion batteries of the present application. The electronic equipment of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0108] Example
[0109] The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0110] Example 1
[0111] Preparation of silicon-carbon materials
[0112] Step 1, obtaining a porous carbon skeleton: the pore volume is 0.7 g / cc, wherein the pore volume of micropores and mesopores is 85%;
[0113] Step 2, subjecting the porous carbon skeleton to a silane deposition reaction to obtain an intermediate product;
[0114] The conditions of the silane deposition reaction include: at 600° C., introducing silane gas with a volume content of 20%, other gas components being nitrogen, and a reaction time of 10 hours.
[0115] Step 3: subjecting the intermediate product to a passivation reaction to obtain the silicon-carbon material.
[0116] The conditions of the passivation reaction include: introducing oxygen with a volume content of 25% at 100° C., with nitrogen as the other gas component, and reacting for 10 hours to obtain the product.
[0117] Power-off test:
[0118] Silicon-carbon material, conductive carbon black and polymer were mixed with deionized water in a mass ratio of 80:10:10 to form a slurry, and a coating with a thickness of 100 μm was applied with a scraper. After drying in a vacuum oven at 85°C for 12 hours, the coating was cut into discs with a diameter of 1 cm using a punch in a dry environment. A metal lithium sheet was used as the counter electrode in a glove box, and a Ceglar composite membrane was selected as the isolation membrane. An electrolyte (the mass ratio of organic solvent EC:PC:DEC = 1:1:1, LiPF 6 The mass percentage is 13%, calculated based on the mass of the electrolyte) and assembled into button batteries. The battery is charged and discharged using the LAND series battery tester to test its charge and discharge performance.
[0119] Test method:
[0120] (1) H element content test
[0121] Weigh an appropriate amount of silicon-carbon material sample, accurate to 0.001 mg, and use Shanghai Microspectrum Organic Element Analyzer for testing, model: American Platinum Elmer SeriesⅡ2400, test method JY / T 0580-2020, and perform parallel determinations twice or more continuously according to the sample determination procedure until the two adjacent results meet the analytical error requirements. After the sample is determined, the standard substance should be determined again. If the result deviates from the instrument operating procedure, the sample should be re-determined. The mass percentage of hydrogen in the sample is calculated according to the following formula: Where e is the absolute mass of hydrogen in the sample obtained from the calibration curve, in mg, m is the weighed mass of the sample, in mg, and k is the calibration factor of hydrogen on the day. The mass percentage of hydrogen is a%.
[0122] (2) Si element content test
[0123] Take 0.1000g silicon-carbon material and put it into a nickel crucible, add 1.5g KOH and cover the crucible, slowly heat the muffle furnace to 400℃, and the heating program is 2h from room temperature to 300℃, 2h from 300℃ to 400℃, start cooling down, digestion program is over, take out the crucible; wait for the crucible after calcination to cool to about 100℃, take it out and put it in an F4 beaker, slowly add 30ml boiling water, soak for 1h, pick up the crucible with tweezers for cleaning, control the volume to 50ml, filter it into a 400ml beaker, pay attention to control the volume of the solution during the transfer process, add 20ml concentrated nitric acid to neutralize the solution at one time after filtration, make the solution acidic, wait for the test solution to cool to room temperature, add solid KCl to saturation under constant stirring, and add 2g in excess, add 10mL fluorine Potassium chloride solution, white precipitate appears after adding potassium fluoride, age for 15 minutes, filter with medium-speed quantitative filter paper, wash the beaker and precipitate with 8mL potassium chloride solution each time, wash three times in total, remove the filter paper and put it back to the original beaker, add 20mL potassium chloride ethanol solution, 10 drops of phenolphthalein, neutralize the residual acid with sodium hydroxide standard solution, stir the filter paper carefully and wipe the cup wall until the solution turns light red, use a glass rod to break up the pulp as much as possible, and make the reaction complete. Add 200mL of neutralized boiling water into the cup (add 10 drops of phenolphthalein after boiling, neutralize with sodium hydroxide standard solution to light red, and titrate with sodium hydroxide standard solution to light red as the end point, and record the titration consumption volume; the silicon content is calculated according to the following formula: Si =(VV 0 )×c×0.0072 / m×100%, where: c is the concentration of sodium hydroxide standard solution, mol / L; V is the volume of sodium hydroxide standard solution consumed in titration, V 0 is the volume of the blank sodium hydroxide standard solution consumed; 0.0072 is the molar mass of 1 / 4 Si; m is the mass of the sample. The mass percentage of silicon element b% is obtained.
[0124] (3) O element content test
[0125] Weigh an appropriate amount of silicon-carbon material sample, accurate to 0.001 mg, and use Shanghai Microspectrum Organic Element Analyzer for testing, model: American Platinum Elmer SeriesⅡ2400, test method JY / T 0580-2020, and perform parallel determinations twice or more continuously according to the sample determination procedure until the two adjacent results meet the analytical error requirements. After the sample is determined, the standard substance should be determined again. If the result deviates from the instrument operating procedure, the sample should be re-determined. The mass percentage of oxygen in the sample is calculated according to the following formula: a=e / m*k, where e is the absolute mass of hydrogen in the sample obtained from the calibration curve, in mg, m is the weighed mass of the sample, in mg, and k is the calibration factor of the oxygen element on the day. The mass percentage of oxygen is obtained as e%.
[0126] (4) Carbon content test
[0127] The silicon-carbon material sample is heated and burned at high temperature in a high-frequency furnace under oxygen-rich conditions to oxidize carbon and sulfur into carbon dioxide and sulfur dioxide. After treatment, the gas enters the corresponding absorption cell, absorbs the corresponding infrared radiation, and then is converted into a corresponding signal by the detector. This signal is sampled by a computer, converted into a value proportional to the concentration of carbon dioxide and sulfur dioxide after linear correction, and then the values of the entire analysis process are accumulated. After the analysis is completed, this accumulated value is divided by the weight value in the computer, multiplied by the correction coefficient, and the blank is deducted to obtain the percentage of carbon and sulfur in the sample. The sample is tested using a high-frequency infrared carbon and sulfur analyzer (Shanghai Dekai HCS-140). The mass percentage of carbon element c% is obtained.
[0128] (5) Hydrogen content test
[0129] Use a 2.5mL gas injection needle to extract 1mL of the upper gas from the above-mentioned vial for GC-TCD testing. The testing equipment is Aglient 7890A, the injection port temperature is 150℃, the constant flow mode is used for splitting, the carrier gas is helium, the column flow rate is 8ml / min, the split ratio is 2:1, the detector temperature is 200℃, the reference flow rate is 30mL / min, and the tail gas flow rate is 4mL / min. The testing principle is to use gas chromatography. When the sample enters the chromatographic column and runs, the components are repeatedly distributed between the two phases. Due to the different adsorption capacities of the fixed phase to each component, after a certain column length, the components are separated from each other, and leave the chromatographic column in the order of outflow and enter the detector for detection. The chromatographic peak outflow curve of each component is drawn on the recorder. By testing the peak area and using the external standard method for quantification, the volume fraction of each component can be determined. That is, the volume percentage x of hydrogen in the mixed gas is obtained.
[0130] (6) Cyclic performance test
[0131] The test temperature is 25 / 45℃, charged to 4.4V at 0.7C constant current, charged to 0.025C at constant voltage, and discharged to 3.0V at 0.5C after standing for 5 minutes. The capacity obtained in this step is taken as the initial capacity, and a cycle test is performed with 0.7C charging / 0.5C discharging. The capacity at each step is compared with the initial capacity to obtain the capacity decay curve. The number of cycles at 25℃ until the capacity retention rate is 90% is recorded as the room temperature cycle performance of the battery, and the number of cycles at 45℃ until the capacity retention rate is 80% is recorded as the high temperature cycle performance of the battery. The cycle performance of the material is compared by comparing the number of cycles in the above two cases.
[0132] (7) Discharge rate test
[0133] At 25°C, discharge at 0.2C to 3.0V, let stand for 5 minutes, charge at 0.5C to 4.45V, charge at constant voltage to 0.05C and let stand for 5 minutes, adjust the discharge rate, and perform discharge tests at 0.2C, 0.5C, 1C, 1.5C, and 2.0C, respectively, to obtain the discharge capacity, compare the capacity obtained at each rate with the capacity obtained at 0.2C, and compare the rate performance by comparing the ratio at 2C and 0.2C.
[0134] (8) Battery full charge expansion rate test
[0135] Use a screw micrometer to test the thickness of a fresh battery at half charge (50% state of charge (SOC)). When the battery is fully charged (100% SOC) after 400 cycles, use a screw micrometer to test the thickness of the battery at this time. By comparing it with the thickness of the fresh battery at the initial half charge (50% SOC), the expansion rate of the fully charged (100% SOC) battery can be obtained.
[0136] (9) First cycle coulomb efficiency test
[0137] The negative electrode material, conductive carbon black and polymer are added with deionized water in a mass ratio of 80:10:10 and stirred into a slurry. A coating with a thickness of 100 um is applied with a scraper. After drying in a vacuum drying oven at 85°C for 12 hours, it is cut into discs with a diameter of 1 cm using a punch in a dry environment. In a glove box, a metal lithium sheet is used as the counter electrode, a Ceglar composite membrane is selected as the isolation membrane, and an electrolyte is added to assemble into a button battery. The battery was charged and discharged using the LAND series battery test, and the test process was as follows: 1. Rest for 4 hours; 2. 0.05C DC To 5mv; 3. 50μA DC To 5mV; 4. Rest for 1 hour; 5. 10μADC To 5mV; 6. Rest for 5 minutes; 7. 0.05C CC To 2.0V; 8. Rest for 5 minutes; 9. 0.2C DC To 5mV; 10. Rest for 5 minutes; 11. 0.2C CC To 2.0V; 12. Rest for 5 minutes; the gram capacity in step 7 divided by the gram capacity in step 5 is the first-cycle coulomb efficiency of the negative electrode material;
[0138] (10) Gram capacity test
[0139] The negative electrode material, conductive carbon black and polymer are added with deionized water in a mass ratio of 80:10:10 and stirred into a slurry. A coating with a thickness of 100 um is applied with a scraper. After drying in a vacuum drying oven at 85°C for 12 hours, it is cut into discs with a diameter of 1 cm using a punch in a dry environment. In a glove box, a metal lithium sheet is used as the counter electrode, a Ceglar composite membrane is selected as the isolation membrane, and an electrolyte is added to assemble into a button battery. The battery was charged and discharged using the LAND series battery test, and the test process was as follows: 1. Rest 4h; 2. 0.05C DC To 5mv; 3. 50μA DC To 5mV; 4. Rest 1h; 5. 10μADC To 5mV; 6. Rest 5min; 7. 0.05C CC To 2.0V; 8. Rest 5min; 9. 0.2C DC To 5mV; 10. Rest5min; 11. 0.2C CC To 2.0V; 12. Rest 5min; the gram capacity in step 7 is the first-cycle discharge gram capacity of the negative electrode material.
[0140] The preparation processes of other embodiments and comparative examples are the same as that of embodiment 1. The difference from embodiment 1 is that the various parameters in the preparation process of silicon-carbon materials are specifically shown in Table a.
[0141] Table a
[0142]
[0143]
[0144] Note: The higher the passivation temperature, the longer the time, the higher the oxygen content, and the lower the hydrogen content.
[0145] Table 1 shows the influence of the mass percentage a of the hydrogen element in the silicon-carbon material and the ratio z of the mass of active hydrogen to the mass of the hydrogen element on gas production, and then on the battery performance. Among them, except for the mass percentage a of the H element in the porous silicon-carbon material, the mass y of the hydrogen atoms (active hydrogen) that can participate in the reaction in the specific test method of claim 1, and its ratio z to the total mass of the H element in the silicon-carbon material, the other parameters are the same as those in the embodiment and the comparative example (see Table 1 for details). Among them, the hydrogen atoms that can participate in the reaction refer to the hydrogen atoms that dissociate into hydrogen gas at 70°C for 48 hours, and the active hydrogen refers to the hydrogen atoms that can participate in the reaction to generate hydrogen gas.
[0146] Table 1
[0147]
[0148] The comparison between Examples 1-6 and Comparative Examples 1-2 illustrates the influence of the mass percentage a of the H element in the porous silicon-carbon material and the ratio z of the mass of hydrogen atoms that can participate in the reaction to the mass of the H element in the silicon-carbon material in the specific test method described in claim 1 on the gas production, and thus on the battery performance. Examples 1-4 and Comparative Example 1 show that when the ratio z of the mass of the active hydrogen to the mass of the total H element in the silicon-carbon material is increased, the gas production value (i.e., the volume percentage of hydrogen in the mixed gas) tested in accordance with claim 1 increases. As shown in Example 4, when the ratio is increased to 26%, the gas production test value is 18%. The surface silicon particles have more -OH, which will cause the loss of active silicon. In Comparative Example 1, the ratio is directly increased to 55%, and the gas production reaches 44%, which greatly deteriorates the cycle performance. Ratio 1 is because the oxygen volume content is only 1%, the surface passivation is insufficient, resulting in excessive active hydrogen; the comparison of Examples 2, 5, 6 and Comparative Example 2 shows that: under the same other conditions, when the mass percentage content of H element a in the porous silicon-carbon material is increased, as shown in Example 6, when it is increased to 4%, there is 18% gas production, and the cycle performance is reduced compared with Examples 2 and 5, while Comparative Example 2 is directly increased to 8%, corresponding to 41% gas production, and the surface silicon material has more -OH, which also greatly deteriorates the cycle performance.
[0149] Table 2 shows the influence of the mass percentage of H element a in the porous silicon-carbon material and the mass percentage of silicon element b in the silicon-carbon material on gas production and thus on battery performance. Among them, except for the mass percentage of H element in the porous silicon-carbon material and the mass percentage of silicon element in the silicon-carbon material, the other parameters are the same between the embodiment and the comparative example (see Table 2 for details).
[0150] Table 2
[0151]
[0152] The comparison between Examples 2, 7-11 and Comparative Examples 3-4 illustrates the influence of the mass percentage a of the H element in the porous silicon-carbon material and the mass percentage b of the silicon element in the silicon-carbon material on the gas production, and then on the battery performance: Under the same other conditions, Examples 2, 7-9 and Comparative Example 3 show that when the mass percentage of the silicon element in the silicon-carbon material is increased, its effect on the gas production is not very large. As the silicon content increases, the gas production increases slightly. The comparison between Examples 2 and 7-8 shows that as the silicon content increases, but the -OH content on the silicon surface is close, the cycle performance improves. When the silicon content is further increased, the factor affecting the cycle performance is introduced. When the silicon content is in an appropriate range, the battery can have better cycle performance and expansion performance.
[0153] Table 3 shows the influence of the mass percentage of carbon element c in the porous silicon-carbon material and the mass percentage of silicon element b in the silicon-carbon material on the battery performance. Among them, except for the mass percentage of carbon element in the porous silicon-carbon material and the mass percentage of silicon element in the silicon-carbon material, the other parameters are the same between the embodiment and the comparative example.
[0154] Table 3
[0155]
[0156] Note: *The discharge capacity in grams of button cell batteries in the first cycle with a discharge cut-off voltage of 2.0V.
[0157] The comparison between Examples 2, 14-19 and Comparative Examples 5-10 illustrates the influence of the carbon content and silicon content of the silicon-carbon material on the battery performance: as shown in Examples 2 and 14-16, when the silicon content of the silicon-carbon material is increased while maintaining the carbon content at 50%, a higher silicon content corresponds to a higher first reversible capacity, and at the same time corresponds to a higher expansion, affecting the cycle performance and expansion performance; in Examples 2 and 17-19, when the carbon content is increased while maintaining the silicon content at 46%, the increased carbon content can provide an effective buffer space for the expansion of the silicon particles, effectively improving the cycle and expansion performance of the battery. When the carbon material content in the comparative example is too high, the expansion of the silicon particles has a good buffer space, and the battery obtains better cycle and expansion performance. However, the lower silicon content cannot effectively exert the advantage of the high energy density of the silicon negative electrode, and when the carbon content in the comparative example is low, it will significantly affect the cycle performance and expansion performance of the battery.
[0158] Table 4 shows the effect of the oxygen content e of the silicon-carbon negative electrode on the battery performance. Except for the oxygen content of the silicon-carbon material, the other parameters between the embodiment and the comparative example are the same.
[0159] Table 4
[0160]
[0161] The comparison between Examples 2, 26-30 and Comparative Examples 11-12 illustrates the effect of the oxygen content of the silicon-carbon material on the battery performance: when other conditions are the same, when the oxygen content of the silicon-carbon material is increased, that is, the oxygen content on the surface of nano-silicon is increased, the increased oxygen content will consume active lithium and form an inert phase, which can effectively improve the expansion performance and increase the cycle life, but when the oxygen content is too high, the initial efficiency and cycle performance will be reduced.
[0162] Table 5 shows the influence of the mass percentage d of lithium hexafluorophosphate in the electrolyte component of the lithium ion battery and the mass y of the active hydrogen in the silicon-carbon material on the battery performance. Except for the mass percentage of lithium hexafluorophosphate in the electrolyte component of the lithium ion battery and the mass y of the active hydrogen in the silicon-carbon material, the other parameters are the same between the embodiment and the comparative example.
[0163] Table 5
[0164]
[0165] The comparison between Examples 2, 33-38 and Comparative Examples 13-15 illustrates the influence of the mass percentage of lithium hexafluorophosphate in the electrolyte components of the lithium ion battery on the battery performance: under the same other conditions, when the mass percentage of the lithium hexafluorophosphate is increased, the lithium hexafluorophosphate can give full play to the role of the lithium salt additive, serve as a bridge between positive and negative lithium ions, effectively improve the lithium ion transfer kinetics, and improve the rate performance. At the same time, rich lithium salts can ensure the bridge effect and maintain the cycle performance. However, when the content is too high, the viscosity of the electrolyte will increase and the lithium ion transfer kinetics will decrease. The comparison between Example 2 and Examples 36-38 illustrates the influence of the mass of active hydrogen in the silicon-carbon material on the battery performance. A low content of active hydrogen is beneficial to improving the cycle performance.
[0166] The silicon-carbon material prepared in this application can significantly improve the cycle, reduce expansion and improve the rate performance after battery performance evaluation.
[0167] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A lithium ion battery, characterized in that: The lithium-ion battery includes a negative electrode plate, which includes a silicon-carbon material. The silicon-carbon material contains hydrogen. Based on the mass of the silicon-carbon material, the mass percentage of the hydrogen element is a%. In the silicon-carbon material, the mass percentage of the silicon element is b%, and the mass percentage of the carbon element is c%, and 0.1≤a≤5, 10≤b≤90, and 10≤c≤80.
2. The lithium-ion battery according to claim 1, characterized in that 0.5 g of the silicon-carbon material was placed in a 36 ml reaction bottle, and stirred at 70° C. for 48 h. The mixed gas in the reaction bottle was obtained, and the volume percentage of hydrogen in the mixed gas was x, 1%≤x≤40%.
3. The lithium-ion battery according to claim 2, characterized in that: Based on the mass of 0.5 g of the silicon-carbon material, the mass of active hydrogen in the silicon-carbon material is y μg, and 4. The lithium-ion battery according to claim 3, characterized in that: In the silicon-carbon material, the ratio of the mass yμg of the active hydrogen to the mass percentage content a% of the hydrogen element is z, z=y / a, satisfying: 2%≤z≤30%.
5. The lithium-ion battery according to claim 4, characterized in that: Satisfies: 3%≤z≤22%.
6. The lithium-ion battery according to claim 1, characterized in that Based on the mass of the silicon-carbon material, the mass percentage of the hydrogen element is a%, and 0.5≤a≤3.
7. The lithium-ion battery according to claim 1, characterized in that: Based on the mass of the silicon-carbon material, the mass percentage a% of the hydrogen element and the mass percentage b% of the silicon element satisfy: 0.001≤a / b≤0.
5.
8. The lithium-ion battery according to claim 7, characterized in that: At least one of the following conditions is met: (1)45≤b≤52; (2)0.01≤a / b≤0.
05.
9. The lithium-ion battery according to claim 1, characterized in that: In the silicon-carbon material, the ratio of the mass percentage content c% of the carbon element to the mass percentage content b% of the silicon element is c / b, which satisfies: 0.1≤c / b≤8.
10. The lithium ion battery according to claim 1, characterized in that: The mass percentage of oxygen element in the silicon-carbon negative electrode material is e%, satisfying: 0.1≤e≤10.
11. The lithium ion battery according to claim 10, characterized in that: Satisfies: 0.2≤e≤6.
12. The lithium ion battery according to claim 3, characterized in that: Based on the mass of the silicon-carbon material, the ratio of the mass y of the active hydrogen to the mass percentage d% of lithium hexafluorophosphate in the lithium ion battery is y / (d%), satisfying: 0.075≤y / (d%)≤55.
13. The lithium ion battery according to claim 12, characterized in that: At least one of the following conditions is met: (1)5≤d≤40; (2)0.5≤y / (d%)≤8.
14. An electronic device comprising the lithium ion battery according to any one of claims 1 to 13.
Citation Information
Patent Citations
Method for preparing silicon oxide (SiOx) / carbon (C) composite materials and prepared silicon carbon cathode materials for lithium ion battery
CN102593426A
Silicon-carbon system lithium ion battery electrolyte and silicon-carbon system lithium ion battery
CN108878976A